Ice-Nucleating Proteins of Bacterial Origin. Report III. Activity Regulation and Significance in Nature and Biotechnology - Gulevsky, A. K.; Relina, L. I. (Problems of Cryobiology and Cryomedicine, 2010)
The information that has been gathered so far on the regulation of bacterial nucleation protein activity is presented in the review; the main fields of applications of biological nucleators and their encoding genes in biotechnology are discussed.